TREATMENT OF GENERALIZED PERIODONTITIS OF INITIAL STAGE IN PEOPLE WHO LIVES IN POLLUTED AREAS OF PRECARPATHIANS - I.Z. Chubij; M.M. Rozhko (Український стоматологічний альманах)
According to the research of a number of scientists in the application of laser therapy with antioxidant quercetin evident recovery system in periodontal tissues, improves blood and lymph circulation, trophic and metabolic processes, inhibites the growth of pathological granulation, reduces congestion and inflammation, shows normalization of cell membrane potential.